2016
DOI: 10.1126/science.aaf3919
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the plant parasite Cuscuta reflexa by a tomato cell surface receptor

Abstract: Parasitic plants are a constraint on agriculture worldwide. Cuscuta reflexa is a stem holoparasite that infests most dicotyledonous plants. One exception is tomato, which is resistant to C. reflexa We discovered that tomato responds to a small peptide factor occurring in Cuscuta spp. with immune responses typically activated after perception of microbe-associated molecular patterns. We identified the cell surface receptor-like protein CUSCUTA RECEPTOR 1 (CuRe1) as essential for the perception of this parasite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 42 publications
2
122
0
Order By: Relevance
“…Interestingly, a small O-glycosylated peptide from a group of parasitic plants belonging to Cuscuta spp. elicits typical immune responses in tomato, suggesting that plants could sense danger not only from microbes but also from invading plants (58). …”
Section: Identification and Characterization Of Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a small O-glycosylated peptide from a group of parasitic plants belonging to Cuscuta spp. elicits typical immune responses in tomato, suggesting that plants could sense danger not only from microbes but also from invading plants (58). …”
Section: Identification and Characterization Of Patternsmentioning
confidence: 99%
“…Sl EIX2 activates defense responses that are suppressed by Sl EIX1 (130). In addition, Arabidopsis RLP30, RLP1, and RLP42 and tomato LRR-RLP cuscuta receptor 1 (CuRe1) are genetically required for the defense responses triggered by SCFE1, eMAX, and PG and the parasitic plant Cuscuta peptide ligand, respectively (58, 65, 169, 170). Tomato LRR-RLPs, Cfs and Ve1, confer resistance against fungal pathogens Cladosporium fulvum and Verticillium dahliae carrying the cognate avirulence proteins, respectively (33, 133).…”
Section: Pattern Recognition Receptor Complexes Perceiving Patternsmentioning
confidence: 99%
“…Recently, a PRR called CuRe1 that recognizes a potential PAMP from the stem of the parasitic plant Cuscuta reflexa was identified in tomatoes, suggesting that a PAMP from parasitic plants can be recognized by other plants, supporting such a hypothesis [31]. In addition, the discovery of cowpea R gene RSG3-301 against Striga gesnerioides , encoding a nucleotide-binding domain and leucine-rich repeat-containing (NLR) receptors, brought the first piece of evidence that an immune receptor can recognize a parasitic plant [32].…”
Section: How Do Parasitic Plants Trigger Immune Responses In the Host?mentioning
confidence: 99%
“…Potentially, ligand binding sites can be engineered at the native gene Often, the isolation of MAMPs is the bottleneck in identifying PRRs [6,9]. However, it is not necessary to structurally identify a MAMP but sufficient to enrich it to a degree that facilitates genetic screenings for the respective PRR [61][62][63]. Furthermore, the identification of various PRRs for chemically diverse types of MAMPs has revealed that plant PRRs are typically RLKs or RLPs.…”
Section: Prr Engineeringmentioning
confidence: 99%